Exit tax adoption to protect Indonesia’s tax base: Are we ready? - Septian Fachrizal; Iva Unnaiza Hanum (Directorate General of Taxes, 2024)
The mobility of individuals, assets, and businesses across international borders is common. This dynamic shift in residency and business structure can lead to significant capital gains, posing tax revenue challenges for nations like Indonesia. The departure of High Net Worth Individuals (HNWI) has brought this issue to the forefront. To address revenue loss due to tax avoidance of that mobility, many countries have adopted exit taxes or exit charges. These measures impose income tax when individuals or businesses change tax residency or transfer assets across borders. This paper conducts a qualitative analysis to explore the adoption of exit taxes in Indonesia, offering policy recommendations to integrate exit taxes into Indonesia's existing tax framework. This paper discusses the idea of exit charge adoption in Indonesia through a qualitative analysis by reference to a comparative study of tax law in various jurisdictions. The study shows that the exit charge adoption is feasible to undertake, considering the existing legal system, Indonesia’s tax regulation, and the simplicity aspect of the taxation system, which Indonesia aims to enhance.